Hubungan Persepsi Siswa tentang Proses Pembelajaran dengan Hasil Belajar di Sekolah Menengah Kejuruan - Al Muzammil; Dwiprima Elvanny Myori (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This study aims to look at the problem of student perceptions about the Learning Process with Student Learning Outcomes in the Subject of Electrical Lighting Installation. The research used was quantitative research which was correlational in nature, the population in this study were 88 students from class XI TITL SMK N 5 Padang. Sampling technique with probability sampling techniques. Instrument trials were conducted on 45 students of class XI TITL at SMK N 5 Padang. The results of the description of the perception data about the learning process, the data obtained shows that the distribution of the answer scores spreads from the lowest score on variable x 54 and the highest score is 84. Based on the distribution of these scores, the average (mean) is 68.11, the middle score (median) is 67 , the number that occurs frequently (mode) 67, and the standard deviation (standard deviation) 7. the results of calculating the value of the correlation coefficient (r) obtained rcount greater than rtable it can be stated that there is a relationship between perceptions of the learning process and learning outcomes of the Information Installation Electricity. From the data analysis it is also known that this relationship is in the strong and significant category.